The Routledge international handbook on hate crime - Hall, Nathan; Corb, Abbee; Giannasi, Paul (Routledge international handbooks, 2018)
pt. 1. Theories and concepts -- pt. 2. The international geography of hate -- pt. 3. Key issues in hate crime -- pt. 4. Combating hate and hate crime.